Strategi Bisnis pada PT CTL Dengan Pendekatan Metode Tows - Tjoe, Tjia Fie; Sarjono, Haryadi (Binus Business Review, 2010)
The purpose of this research is determining direction of the correct business strategy to be applied by PT CTL, a garment company producing cloth for men. Research method used by the author is descriptive analysis with a case study research method. Research is conducted by collecting data obtained through survey by interview and giving questionnaire to all staff and head and also observation by evaluating directly the research object and also through literature study. Data analysis is conducted through input phase by using IFAS and EFAS matrix, adaptation phase with TOWS diagram, TOWS matrix and Internal-External matrix, and also uses SPACE matrix and also BCG matrix to analyse companys finance situation. Based on the conducted analysist the recommended corporation level strategy to be used by the company is diversification strategy direct to growth and stability.Â